Utilization of Social Media as Digital Educational Content (A Case Study on the Utilization of Social Media as Digital Educational Content about History on Twitter @Neohistoria_Id). - Reza, Faisal; GB, Nur Tsabita; Lathifah, Nisa (Yayasan Sinergi Kawula Muda, 2023)
Social media or online media is used by its users to communicate, interact, share, network, and learn digitally by utilizing the features available on social media. The purpose of this study is to understand the communication planning process, followers' responses, and the reasons why @neohistoria_id uses Twitter as a medium for digital history education. This research employs a qualitative method with a case study approach and uses Regina Luttrell's Circular Model of SOME. The technique for selecting informants is purposive sampling. The communication planning process carried out by @neohistoria_id involves several stages. The first stage is sharing, where the Twitter account @neohistoria_id participates in sharing historical content. The public who receive this content are connected with @neohistoria_id, so @neohistoria_id must build trust with the public to keep them reading their content. In the optimization stage, @neohistoria_id listens to and learns from the public discussions about their posts. Then, @neohistoria_id takes part in these discussions through replies or Twitter Spaces. In the management stage, @neohistoria_id conducts media monitoring to delve into current issues. Following this, @neohistoria_id must respond quickly to create real-time interaction with the public. In the engagement stage, @neohistoria_id understands how to build relationships with the public (influencer relations). The goal is to identify the target audience of @neohistoria_id, which includes students and professionals. This is important to find a similar audience and encourage positive changes in the image built by the Twitter account @neohistoria_id itself.